Impact of climate change on natural hazard-induced disasters in Latin America and the Caribbean - Aizaga, Miguel; Baldeón-Egas, Paúl Francisco; Toasa, Renato M. (Frontiers in Climate, 2025)
Climate change-related disasters represent nature’s response to the severe and cumulative damage generated by human activities. This article aims to examine such impacts by categorizing Latin American and Caribbean countries according to the number and type of natural hazard-induced disasters recorded between 2000 and 2022, and by assessing the correlation between disaster frequency and national greenhouse gas (GHG) emissions. The study adopts a documentary design with a quantitative and correlational approach. Data were obtained from the International Monetary Fund and Climate Watch Data. Analytical techniques include clustering, principal component analysis (PCA), and Pearson’s correlation coefficient. The clustering procedure identified five groups of countries, each characterized by distinct patterns in both the type and frequency of disasters. Findings reveal that Mexico, Brazil, and Colombia are the most affected countries. The PCA results highlight two principal dimensions: (1) hydrological events (floods, droughts, storms, and landslides) and (2) thermal phenomena (extreme temperatures and wildfires). Pearson’s correlation analysis demonstrates a moderate yet significant positive association between the incidence of climate change-related natural hazard-induced disasters and GHG emissions. This suggests that, although certain countries combine high levels of emissions with a high frequency of disasters, there are also countries with high disaster occurrence that are not among the largest GHG emitters.